Implications of the evacuation of hospitalized patients in a nuclear emergency - Yasuda, Hiroshi (Frontiers in Public Health, 2023)
In the accident at the Fukushima Daiichi nuclear power station following the Great East Japan Earthquake and tsunami, more than 50 hospital patients died during or soon after evacuation, primarily owing to the interruption of necessary medical care. To prevent the occurrence of such losses in the future, focus should be on the health status of an individual patient in decisions regarding evacuation, which is currently based on non-human aspects, that is, the geophysical conditions and status of the accident facility. In this brief research report, the author provides a conceptual basis for making more appropriate decisions on the evacuation of hospitalized patients by balancing radiological risk and evacuation-induced health risk considering the principle of justification. This report is expected to foster discussions among stakeholders to protect vulnerable people more appropriately in nuclear emergency situations.